Optical Properties of Tap Water Purity using He-Ne Laser with Different Power Density - Al-Azzawi, Zeena M; Abdulzahra, Narges Zamil; Hammood, Iman H (Al-Nahrain Journal of Science, 2018)
Tap water differs from pure water, it contains more chemical contents arise in drinking water, it effect on health concern only after extended exposure of years, rather than months. The purpose of this article is to study the optical properties of tap water by using different power density from He-Ne laser beam transport through some samples. These samples of water mostly contain NaCl salts and clay .When we increasing concentration and sample length we can observed that decreasing transmittance ,(absorption and extinction) coefficients while the absorbance will be increased .At the 5 cm sample length we observed that tap water has transmittance about 17%, while NaCl (0.7) concentration has 58%,clay solute has 2%, and mixing from (0.7 NaCl and 0.15 clay) concentrations has transmittance 8%, The absorbance and absorption coefficient of tap water is greater than NaCl and less than clay alone and mixing (clay with salt) at the same sample length.